When justice comes - Coble, Colleen; Acker, Rick, 1966- (Coble, Colleen. Tupelo Grove novel, 2026)
"Hez and Savannah Webster have survived storms that would bury others without a love as strong as theirs -- but can they withstand the final battle in the deadly Legare-Willard feud that threatens to sweep away everything they've fought for? Hezekiah "Hez" Webster and his fiancée, Savannah, stand on the brink of a new life, but their dreams are haunted by specters of the past. Just as they're getting ready to adopt her nephew, two other petitioners also file for custody -- both of whom only want Simon for their own gains. Between the financial company that Hez outmaneuvered to save the university from ruin and the bad blood from the head of the Willard family, it's hard to say who wants them out of the way more. Hez and Savannah's quest for justice leads them through a labyrinth of family law, where loyalties are tested and trust is a dangerous luxury when every decision could be their last. With the clock ticking, Hez and Savannah must confront the ghosts of their past and their deepest fears to secure a future for Simon. But with every secret revealed, the stakes grow higher. Can they build the family they've always dreamed of, or will their enemies succeed in tearing them apart forever?" --